2009
DOI: 10.3921/joptom.2009.127
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Low Vision and Musculoskeletal Complaints. A Case Control Study Between Age-related Macular Degeneration Patients and Age-matched Controls with Normal Vision

Abstract: INTRODUCTION:Age-related Macular Degeneration (ARMD) patients often describe complaints from neck and scapula area muscles and a decreased postural control. In clinical assessment, these complaints are considered to be due to old age. PURPOSE: This study focuses on low-vision patients with ARMD, comparing them to age-matched controls without any eye disease, in order to evaluate if the linkage between self-rated visual complaints and musculoskeletal complaints is more prominent when low vision is present. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…A case to item ratio of 5:1 is regarded adequate 50. In the current study, the ratio was 83:1 compared to the 3:1 in the original study 24. The use of Rasch analysis in the present study enabled a detailed examination of the operation of each VMB domain, corresponding with the notion that Rasch analysis is an important tool in instrument development in vision science 51.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A case to item ratio of 5:1 is regarded adequate 50. In the current study, the ratio was 83:1 compared to the 3:1 in the original study 24. The use of Rasch analysis in the present study enabled a detailed examination of the operation of each VMB domain, corresponding with the notion that Rasch analysis is an important tool in instrument development in vision science 51.…”
Section: Discussionmentioning
confidence: 60%
“…Items were refined after patient and expert reviews to achieve face validity. From a pool of items, 15 were deemed representative by the research group and were tested on patients with age-related macular degeneration 24. Principal component analysis (PCA) resulted in a three-factor solution comprising visual, musculoskeletal, and balance complaints.…”
mentioning
confidence: 99%
“…In primary health care these symptoms are often downplayed as part of the aging processes [18] and not typically associated with visual impairments [6, 19]. However, research indicates that people suffering from AMD may pose a higher risk of developing visual, musculoskeletal, and balance complaints [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous research addressing the impact of visual loss in AMD patients on visual, musculoskeletal, and balance complaints is limited or has used cross-sectional design [20]. This research has identified concurrent relationships; however, less is known about the influences of visual decline in AMD on visual, musculoskeletal, and balance complaints across time.…”
Section: Introductionmentioning
confidence: 99%
“…5 Age-related macular degeneration is associated with more visual stress and an increase in musculoskeletal complaints. 6 Poor vision is an important predictor of falls 7 with poor visual acuity, contrast sensitivity, stereopsis and visual impairment all increasing the frequency of lost balance 8,9 and the degeneration of coordination that results from decreased spatial orientation and awareness. Interestingly, the Morse Falls Scale Assessment, 10 which is a standardised instrument used for intake into some hospital settings, does not include any questions on vision.…”
mentioning
confidence: 99%